Peningkatan Kompetensi Menggambar Teknik Siswa SMK PUSTEK Melalui Pelatihan Perangkat Lunak AutoCAD - Maulana Akhsan; Jaja Miharja; Moehammad Denny Nusa Putra (CV. ITTC INDONESIA, 2026)
Technological and industrial advancements require Vocational High School (SMK) graduates to have adequate technical competencies to be ready for work. However, students' competence in computer software mastery, specifically in the Light Vehicle Engineering department at SMK PUSTEK, remains relatively low. Many students are not yet proficient in operating AutoCAD software, even though the automotive industry highly depends on it for precisely designing body and engine components in 2D and 3D formats. The purpose of this community service activity was to provide basic training in operating and technical drawing using AutoCAD software to 12th-grade students at SMK PUSTEK to enhance their technical competencies and work readiness. The implementation method consisted of several stages: program socialization, theoretical material presentation (lecture), direct demonstration by instructors, guided drawing practice, as well as discussion and evaluation sessions. Success analysis techniques were conducted through quantitative measurement of participants' practical task completion and qualitative observation. The results showed that the training ran very smoothly and received a positive response. A total of 20 participating students successfully demonstrated an improvement in basic technical drawing understanding and skills, evidenced by achieving a practical performance score above 75 and their success in completing AutoCAD drawing instructions independently. Student enthusiasm was also evident from their active participation during the discussion sessions.